Pengaruh Persepsi Auditor Junior dan Auditor Senior atas Sistem Pengendalian Mutu Kantor Akuntan Publik (KAP) Terhadap Kinerja Auditor - Verani Carolina; Christine Dwi Karya; Riki Martusa (Jurnal Akuntansi, 2011)
The objective of this research is to determine the impact of auditor perception through “Sistem Pengendalian Mutu” (independent variables) on auditor performance (dependent variable). The study also make the different between the perception of junior auditors and senior auditors. The respondent of this research are 38 auditors from 7 Public Accountant Firm in Bandung. The research used hypotesis test while data were processed by Statistical Package for the Social Sciences (SPSS) program. It is using regression analysis to examine the effect of auditor perception through “Sistem Pengendalian Mutu” on auditor performance. Independent sample t-test is used to compare junior auditor and senior auditor performance. The result of this research shows that perception of “Sistem Pengendalian Mutu” give positive effect to auditor performance. The independent sample t-test indicates that junior auditors performance is better than senior auditor performance through their perception of “Sistem Pengendalian Mutu”.Keywords: auditor perception, auditor performance